Penerapan iptek melalui kukerta terintegrasi guna mengakselerasi pengembangan wisata bahari di Kelurahan Kampung Baru, Kecamatan Senapelan, Kota Pekanbaru - Muhammad Fauzi; Eko Prianto; Budijono Budijono; Iskandar Putra; Muhammad Farhan Surez; Zuriati Murni (Unri Conference Series: Community Engagement, 2020)
Kampung Baru is one of the villages in Pekanbaru city that has the potential to develop large marine tourism. Its strategic location on the coast of Siak River and has a cultural reserve "RumahBatin" makes Kampung Baru as one of the new destinations of future historical tourism. The existence of Kampung Baru as a tourist destination is still not well exposed so there needs to be a touch of Science and improvement to accelerate its development. The purpose of this activity is to accelerate the development of marine tourism in Kampung Baru Village, Pekanbaru City. The method used is a survey method to identify activities and counseling methods to convey Science to the community. The stages of the implementation of the activity are divided into three stages of preparation, implementation and evaluation. The results of a quick survey conducted, to accelerate the development of marine tourism activities in Kampung Baru through the socialization of halal certificates, making and dividing trash cans, making and enforcing plank boards, planting trees and vegetable seedlings and cleaning inner houses. The implementation of the activity is doing well and on target this can be seen from the community and village officials in supporting this activity. With the integrated KUKERTA (Community Service), the neglected tourism potential of Kampung Baru can be reappointed as a marine tourism. This leads to the fact that the touch of Science through integrated KUKERTA (Community Service) is able to accelerate the development of marine tourism in Kampung Baru.